2012
DOI: 10.3390/su4081733
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Litter Generation and Littering Practices in a Mexico City Neighborhood

Abstract: Urban litter is generated by human societies everywhere. Some litter is recyclable waste. In this study, the acronym RMSW is used to refer to recyclable municipal solid waste generated in streets. Public attitude towards RMSW generation, generators' perceptions, and quantification of RMSW in streets were examined in a Mexico City neighborhood, where litter presence causes major environmental problems affecting the population year after year. Interviews with neighborhood residents and item counts were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Litter has been shown to be generated by a number of factors, most of which are related to the individual. Multiple studies have found that laziness is perceived to be a primary generator of litter (Muñoz-Cadena et al, 2012; Ojedokun & Balogun, 2011). On average, men (Meeker, 1997) and nonmarried individuals (Al-Khatib et al, 2009) produce more litter relative to women and married couples.…”
Section: Factors Related To Litteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Litter has been shown to be generated by a number of factors, most of which are related to the individual. Multiple studies have found that laziness is perceived to be a primary generator of litter (Muñoz-Cadena et al, 2012; Ojedokun & Balogun, 2011). On average, men (Meeker, 1997) and nonmarried individuals (Al-Khatib et al, 2009) produce more litter relative to women and married couples.…”
Section: Factors Related To Litteringmentioning
confidence: 99%
“…Literature also indicates that the environmental setting plays an important role in explaining littering behavior. For example, multiple studies have found that the lack of trash receptacles or bins is associated with the presence of rubbish (Finnie, 1973; Muñoz-Cadena et al, 2012; Schultz & Stein, 2009). Generally, as the availability of trash receptacles decreases, levels of litter increase (Schultz & Stein, 2009).…”
Section: Factors Related To Litteringmentioning
confidence: 99%
“…We can object to that currently the efficiency of those acting against littering is not high, so even a better enforcement of the currently valid rules could somewhat help. As already indicated, the Mexican study (Muñoz-Cadena et al, 2012: 1741 showed that almost one quarter of interviewed offenders claimed to have littered due to the lack of vigilance by municipal authorities. So, the statement on the efficiency can be considered true.…”
Section: Catching a Litterermentioning
confidence: 91%
“…al., 1972: 1). Another study published in that century also pointed to the significance of the lack of vigilance by municipal authorities (Muñoz-Cadena et. al., 2012: 1741.…”
Section: Why Do People Littermentioning
confidence: 95%
“…The local economies of coastal communities might also be negatively impacted by the aesthetics of plastic pollution since litter deters visitors from beaches and more frequent cleanups are required to maintain optimal levels of tourism and recreation (Sheavly and Register, 2007). The presence of plastic debris on beaches then also increases the collection and total disposal cost of beach litter for coastal communities, which negatively affects their economies (Muñoz-Cadena et al, 2012).…”
Section: Impacts Of Plastic Pollutionmentioning
confidence: 99%